Pathway-specific GABAergic inhibition contributes to the gain of resilience against anorexia-like behavior of adolescent female mice - Aoki, Chiye; Santiago, Adrienne N. (Frontiers in Behavioral Neuroscience, 2022)
Anorexia nervosa is one of the most debilitating mental illnesses that emerges during adolescence, especially among females. Anorexia nervosa is characterized by severe voluntary food restriction and compulsive exercising, which combine to cause extreme body weight loss. We use activity-based anorexia (ABA), an animal model, to investigate the neurobiological bases of vulnerability to anorexia nervosa. This is a Mini-Review, focused on new ideas that have emerged based on recent findings from the Aoki Lab. Our findings point to the cellular and molecular underpinnings of three ABA phenomena: (1) age-dependence of ABA vulnerability; (2) individual differences in the persistence of ABA vulnerability during adolescence; (3) GABAergic synaptic plasticity in the hippocampus and the prefrontal cortex that contributes to the suppression of the maladaptive anorexia-like behaviors. We also include new data on the contribution to ABA vulnerability by cell type-specific knockdown of a GABA receptor subunit, α4, in dorsal hippocampus. Although the GABA system recurs as a key player in the gain of ABA resilience, the data predict why targeting the GABA system, singularly, may have only limited efficacy in treating anorexia nervosa. This is because boosting the GABAergic system may suppress the maladaptive behavior of over-exercising but could also suppress food consumption. We hypothesize that a sub-anesthetic dose of ketamine may be the magic bullet, since a single injection of this drug to mid-adolescent female mice undergoing ABA induction enhances food consumption and reduces wheel running, thereby reducing body weight loss through plasticity at excitatory synaptic inputs to both excitatory and inhibitory neurons. The same treatment is not as efficacious during late adolescence but multiple dosing of ketamine can suppress ABA vulnerability partially. This caveat underscores the importance of conducting behavioral, synaptic and molecular analyses across multiple time points spanning the developmental stage of adolescence and into adulthood. Since this is a Mini-Review, we recommend additional literature for readers seeking more comprehensive reviews on these subjects.